Unionism and the education sector in Zimbabwe 1980 to ZIMTA Warren/Park Mabelreign District - Mhizha, Edwin (2017)
The paper examines Trade Unions the role they have been playing in promoting good working conditions passable remuneration for employees in Zimbabwe since 1980 till date. The idea became necessary in view of the unending political, economic, social, educational, and electoral problems bedevilling trade unions resulting poor performance. The country Unionism commenced the colonial error with the aim and objective of protecting employees from exploitation and oppression by employers since there is conflict of interest between employers and employees. Employees’ motives are driven by profit and employee’s motivation is driven by salary maximization and incentives. Trade Union acts as mediators between the employer and employees in work environment and has played a pivotal role in bettering employees in Zimbabwe. The aim of the study was to assess the effectiveness of trade unions in presenting the interests and grievance of workers. However, there is gnashing of teeth and an outcry from employees over poor representation by trade unions, corruptionand political interference and concentration by union leaders giving a blind eye to workers grievances. It aims of this study to rejuvenate the ills bedevilling trade union operation and poor representation of employees. The research would be qualitative in nature and target Warren Park/ Mabelreign District as the area for a case study. The research targets people who are formally employed in both public and private sector and trade union officials and are relevant people since they are the ones facing these challenges. The outcome of the study can be used as a panacea to the problems affecting the environment of work in Zimbabwe in coming up with measure and policies that arrest these challenges.